Implementasi Mekanisme End-To-End Security Menggunakan Algoritma AES dan HMAC pada Pengiriman Data Sensor ECG Berbasis LoRa - Al Ghitha Aulia Rahman; Eko Sakti Pramukantoro; Kasyful Amron (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
LoRa (Long-Range) is a wireless transmission media that was designed to be used on low-powered devices such as sensors and only needs to transmit small data over long distances. The application of LoRa in IoT-based ECG (Electrocardiogram) monitoring will assist patients. However, one of the main challenges in implementing IoT is its data security. Moreover, health data such as ECG data are considered to be sensitive because they are used in medical diagnosis. Therefore, a solution to this vulnerability is implementing a security mechanism between endpoints (end-to-end security). End-to-end security mechanisms can be implemented using cryptography. In this research, an end-to-end security using AES and HMAC algorithm is implemented. AES and HMAC is chosen because the devices that is used are low-powered and only have limited resources. That mechanism is applied to sensor nodes and gateway because they are the endpoints.In this research, an end-to-end security mechanism has been implemented successfully. But, the application of this end-to-end security mechanism has an impact, that is an increase in end-to-end delay that exceeds the tolerated delay limit in ECG data transmission. So, this mechanism isn't recommended to be applied in ECG data transmission.